Are Museums Allowed to Keep a Secret?: Secret and Sacred Objects at the Weltmuseum Wien. Issue 1 (1st July 2021) - Bottesi, Anna
Abstract: Today many ethnographic museums are questioning the hierarchical power relationships implicit in the act of representing the cultures of others. In this article I analyze the way that the curator of the South American section of the Weltmuseum Wien chose to deal with the exhibition of sacred and secret objects, that is, those things that only specific categories of individuals are allowed to view. If we exclude storage as a possible solution, what is the proper way to treat artifacts such as these? How should the expectations of an audience attracted to the idea of the exotic, and perhaps forbidden, be satisfied? How can this challenge be transformed into an opportunity to reflect about what we have, or have not, the right to do?